Chinese Private Higher Education Under Pressure: Quality, Policy, and Demographic Decline - Gong, Cassidy (International Higher Education, 2025)
<h3 id="situated-at-the-bottom-of-the-echelon-in-the-highly-stratified-chinese-higher-education-system-private-higher-education-phe-faces-existing-challenges-while-being-confronted-with-new-uncertainties-that-threaten-its-survival-this-article-discusses-the-persistent-quality-improvement-challenge-and-an-increasingly-volatile-policy-environment-that-chinese-phe-faces" data-pm-slice="1 1 []">Situated at the bottom of the echelon in the highly stratified Chinese higher education system, private higher education (PHE) faces existing challenges while being confronted with new uncertainties that threaten its survival. This article discusses the persistent quality improvement challenge and an increasingly volatile policy environment that Chinese PHE faces.